Avaliação da funcionalidade ecológica de uma área em processo de restauração no bioma da Mata Atlântica, Rio de Janeiro - Altivo, Felipe de Souza (2015)
The restoration should involve the return of vegetation cover and ecological processes. This study aims to assess whether the restoration of diversity also promoted the recovery of the ecological functionality of an area located in the Atlantic Forest, in Rio de Janeiro. During the study, a set of ecological functionality of indicators based on community diversity, its structure and its context in the landscape were analized. The most efficient indicators for evaluation of the areas were the structure (density, height and basal area), followed by diversity and evenness (H 'and J). Between the 5th and 20th month, there was a significant reduction of diversity, further for families than for the species. However, indicators of ecological functions did not change between the ages despite the reduction in diversity, showing that there was redundancy of functions between different species. The results suggest the deployment of fewer species maintaining the proportion of the functional diversity of species can optimize the actions of forest restoration for promoting the reduction of mortality, therefore generating greater increase in community structure. The regenerating analysis showed the importance of faunal interactions in forest restoration activities, since 77% of regenerating species found in the area have zoochorous dispersion syndrome.